Experience of VBAC in A Private Hospital - Akter, Marufa; M, Ferdousi; J, Sultan; Rahman Rrb, Ratu Rumana Binte (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Vaginal birth after cesarean section (VBAC) for a non-recurring indication has been described by several authors as safe & having a success rate of 60-80%. VBAC increases the possibilities of subsequent vaginal deliveries & reduces the rate of repeat cesarean section with associated postoperative morbidity. Objective: To estimate the success rate & risks of an attempted vaginal birth after one cesarean delivery (VBAC). Materials & Methods: The study was conducted as a private hospital based cross sectional descriptive study from July2021 to December 2021. Total 176 patients were admitted with history of prior CS in this study. Among these cases common indications of primary CS were caesarean delivery on maternal request (CDMR), fetal distress, less fetal movement etc. All cases with previous one cesarean section who delivered vaginally within the study period comprised the study population. Women with 1 previous cesarean section, singleton pregnancy, cephalic presentation & term gestation were included in this study. However, women with history of 2 or more C/S, previous uterine surgery like myomectomy & classical C/S were excluded. Result: Out of 37 cases enrolled in the study, 24 (64.86%) successfully delivered vaginally without any complication. 11(29.73%) cases needed repeat cesarean section and 2 (5.41%) cases had to undergo emergency cesarean section for scar tenderness, those were found to be uterine scar rupture. Conclusion: This study suggested that trial of labour after caesarean section (TOLAC) was effective in decreasing CS in this study population. TOLAC and VBAC can be offered to pregnant women without contraindication. To establish the finding definitively, large multicenter prospective studies are required. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 28-31